Peran Ojk Dalam Proses Pengembalian Dana Nasabah Bank Yang Hilang Dan Keseuaiannya Dalam Perspektif Islam - Rizky Maharani Prastita (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2018)
and the continuity of the bank's business activities. This trust must be maintained since the main capital of the bank comes from the public savings funds. In these days, many cases of loss of funds deposits due to fraud committed by the bank. The purpose of this study is to explain the role of the Financial Services Authority in the process of refunding customer deposits lost. Indonesian Government has established an independent institution which has the authority to do the regulations, supervision, inspection, and investigation of banks deemed to be detrimental to their customers. The role of the Financial Services Authority in the process of refunding customer deposits lost is by providing facilities that enable banks and customer to solve their problem by providing the tools to conduct customer complaints, make mecanism of customer complaints, and also facilitate customer complaints. The Financial Services Authority may also instruct or perform certain actions to the bank in order to resolve customer complaints, to file a lawsuit to recover funds that deposited by customers from the bank, whether under the control of the bank or other parties in good intention, or obtaining compensation from the bank. The overall activities of the OJK are in accordance with Islam.